EXPLOITING OF INTERNET AS SUPPORTER OF PREPARATION OF STUDY AT MAN SALIDO KECAMATAN IV JURAI PESISIR KABUPATEN PESISIR SELATAN - Amalia, Ririn; Adiyalmon, Adiyalmon; Prahara, Surya (Pendidikan Sosiologi, 2013)
Effective study will be created if target of study have been reached. For the shake of reaching of target of study hence needed preparation before study process take place. Internet represent a information media and of komonikasi able to assist teacher in preparation of study. hence as a teacher claimed can exploit technology of internet for the shake of reaching of target of study. Formula research internal issue Exploiting Of Internet As Supporter of Preparation of Study Madrasah Aliyah Negeri Salido Kecamatan IV Jurai Kabupaten Pesisir Selatan. This Research aim to to lay open Exploiting Of Internet As Supporter of Preparation of Study Madrasah Aliyah Negeri Salido Kecamatan IV Jurai Kabupaten Pesisir Selatan.This research represent research qualitative with approach of descriptive research. Technique which used in election of informan sampling snowball that is student and teacher. its Data type him 1) Primary data that is collected data interview with informan 2) data of Sekunder that is collected data indirectly. Technique used for data collecting by observation, interview and have the honour to documentation. Technique analyse data used by 1) Data discount 2) Display Data 3) Decision making and verification.From result of this research expressed that internet have been used by student and teacher of MAN Salido as 1) internet used as the source of teaching materials, searching study items like picture, simple attempt and cycle 2) internet used as study media not langsunguntuk present study items in the form of short video or picture to be taught 3) internet used student as source learn to look for items, making duty like handing out, kliping and also also used as social jejaring like entertainment amusement and facebook